Literasi Keuangan, Pendapatan dan Gaya Hidup terhadap Pengelolaan Keuangan di Masa Pandemi - Siti Muntahanah; Heru Cahyo; Heri Setiawan; Sindi Rahmah (Universitas Batanghari Jambi, 2021)
This study aims to determine the effect of financial literacy, income and lifestyle on financial management behaviour during a pandemic. This type of research is quantitative research and the data used are primary data obtained from questionnaires, interviews and observations. The population of this research is member of Koperasi Pesat in Sumbang and Baturraden Districts, using a sample of 47 respondents. The sampling technique is simple random sampling. The analytical method used is a multiple linear regression method. The results of the study partially show that variable income have a signifficant positive effect on financial management behaviour. While variable financial literacy and lifestyle insignificant effect on financial management behavior.